Sport as a regulator for cardiovascular risk factor. Differences attending to gender - Mª Pilar Catalán Edo; Enrique Serrano Ostariz (Fundación para el Desarrollo de la Enfermería, 2013)
Objective: Study if the sports practice means visible and quantifiable benefits to the health of people who practice, if there are differences between sexes and motivations to follow a life active.Metodology: Cross-sectional study in the field of primary health care. We selected 100 subjects (50% women) aged between 30 and 60 years, distributed in 2 groups, depending on whether or not to perform physical activity. Main measurements: Index of body mass, blood pressure, cholesterol (LDL-C, HDL-C), triglycerides, glucose, tobacco consumption (cigarettes/day), and level of stress.Results: In the Group of women is significant differences (p < 0,05) between the different age ranges for BMI, TA, cholesterol and triglycerides, not appreciating these men. Active women have lower averages of cholesterol, LDL-C, and stress that the sedentary and older of HDL-C, being these significant differences (p < 0,05). Active men also under TAS, and triglycerides than the sedentary figures still these significant differences (p < 0,05).Conclusions: The practice of aerobic exercise, could interfere with cardiovascular risk factors and contribute to reducing the prevalence of cardiovascular disease secondary to the population, but the benefits are not equal in men that women, which requires further reflection and specific actions in each group by health professionals, possible thanks to the motivation of the population to continue an active life.